Telomere Length Measurement by Molecular Combing - Kahl, Vivian F. S.; Allen, Joshua A. M.; Nelson, Christopher B.; Sobinoff, Alexander P.; Lee, Michael; Kilo, Tatjana; Vasireddy, Raja S.; Pickett, Hilda A. (Frontiers in Cell and Developmental Biology, 2020)
Telomeres are repetitive regions of DNA bound by specialized proteins at the termini of linear chromosomes that prevent the natural chromosome ends from being recognized as DNA double strand breaks. Telomeric DNA is gradually eroded with each round of cell division, resulting in the accumulation of critically short or dysfunctional telomeres that eventually trigger cellular senescence. Consequently, telomere length is indicative of the proliferative capacity of a cell. Multiple methods exist to measure telomere length and telomere content, but a simple and reliable technique to accurately measure individual telomere lengths is currently lacking. We have developed the Telomere length Combing Assay (TCA) to measure telomere length on stretched DNA fibers. We used TCA to measure telomere erosion in primary human fibroblasts, and to detect telomere lengthening in response to activation of telomere maintenance pathways. TCA was also used to accurately measure telomere length in healthy individuals, and to identify critically short telomeres in patients with telomere biology disorders. TCA is performed on isolated DNA, negating the need for cycling cells. TCA is amenable to semi-automated image analysis, and can be fully automated using the Genomic Vision molecular combing platform. This not only precludes sampling bias, but also provides the potential for high-throughput applications and clinical development. TCA is a simple and versatile technique to measure the distribution of individual telomere lengths in a cell population, offering improved accuracy, and more detailed biological insight for telomere length measurement applications.